2012
DOI: 10.1161/circinterventions.112.968321
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Pilot Study of Autologous CD34+ Cell Therapy for Critical Limb Ischemia

Abstract: Background Critical limb ischemia (CLI) portends a risk of major amputation of 25-35% within 1 year of diagnosis. Pre-clinical studies provide evidence that intramuscular injection of autologous CD34+ cells improve limb perfusion and reduce amputation risk. In this randomized, double-blind, placebo-controlled pilot study, we evaluated the safety and efficacy of intramuscular injections of autologous CD34+ cells in subjects with moderate or high-risk CLI who were poor or non-candidates for surgical or percutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
145
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(158 citation statements)
references
References 26 publications
4
145
1
4
Order By: Relevance
“…Second, the outcomes in the three ASO patients we reported on in our pilot study appeared to be poor 4. All of the ASO patients underwent major amputations within 3 months after PuCeT, similar to the disappointing results from ASO patients in other studies 2, 8. In contrast, the outcomes of AICLI patients showed extreme promise.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Second, the outcomes in the three ASO patients we reported on in our pilot study appeared to be poor 4. All of the ASO patients underwent major amputations within 3 months after PuCeT, similar to the disappointing results from ASO patients in other studies 2, 8. In contrast, the outcomes of AICLI patients showed extreme promise.…”
Section: Discussionsupporting
confidence: 72%
“…As one of the stem cell therapies, PuCeT has demonstrated encouraging outcomes 2, 3. Similarly, in our pilot study conducted from 2009 to 2011, PuCeT demonstrated favorable early outcomes in AICLI 4.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The CD34 + stem cell fraction of adult human peripheral blood has already been used in two preclinical trials of therapeutic angiogenesis for PAD. One trial showed significant improvements in the efficacy scores (toe-brachial pressure index, pain scale, and total walking distance); however, the other study showed no effect on amputation rates [25,26]. Neither trial reported any treatment-associated adverse events; thus, the safety and feasibility of ECFC-based therapy can be considered established.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the last several years suggest that endothelial impairment substantially contributes to the onset and progression of and recovery from inflammatory conditions [1]. EPCs, derived from bone marrow hematopoietic stem cells, (HSCs) have the capability to migrate to the site of endothelial damage through the peripheral circulation and have been used to treat several inflammatory diseases, ischemic limb disease, peripheral vascular disease, and coronary heart disease [6][7][8].…”
mentioning
confidence: 99%